Understanding social-ecological change and transformation through community perceptions of system identity - Andrachuk, Mark; Armitage, Derek (Ecology and society, 2015)
We developed an empirical approach to consider social-ecological system change and transformation by drawing on resource users’ knowledge and perceptions. We applied this approach in the Cau Hai lagoon, a coastal area dominated by small-scale fisheries in central Vietnam. Nine focus groups with more than 70 fishers were used to gather information about key social-ecological system elements and interactions, historical social-ecological dynamics, and possible thresholds between distinct social-ecological system identities. The patterns of change in livelihoods and resource exploitation in the Cau Hai lagoon are similar to those seen in other coastal lagoon and small-scale fishery contexts. Our findings show some promise for the use of local knowledge and the perceptions of resource user communities to understand and characterize social-ecological transformations. Importantly, however, we also demonstrate how social-ecological transformations are complicated processes driven by many factors beyond the control of any singular individual or group. We argue that (1) the occurrence of social-ecological transformations can result in either positive or negative outcomes and (2) that we need to direct our thinking away from drawing tidy conclusions about if and when social-ecological transformations take place. Our research also encourages scholars to carefully consider how we frame the benefits of participatory, community-based governance initiatives. Importantly, we need to examine the ways that governance initiatives will be beneficial for some people and detrimental for others, and we need to be fully aware of locally contested interests and acknowledge competing priorities for fisheries management and human well-being. Community-oriented assessments informed by resilience thinking can help to open up questions about economic, political, cultural, and environmental aspects of undesirable path dependencies and traps.